Pengembangan Sistem Layanan Informasi Berbasis Web dengan Memanfaatkan AI Pada ChatGPT - Budiman, Aji Wahyu; Setiawan, Agus; Nugroho, Setiya (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
Artificial intelligence (AI) has become one of the major contributors to the development of technology in the current era. One example is chatbot technology. On November 30, 2022, the leading technology company, OpenAI, launched ChatGPT, a conversational AI. The focus of concern in this context is the information service in Tegalrejo Village Government, which does not have an online information platform, causing issues such as the service being individualized and not widely distributed, making it ineffective. Accessing the service requires a visit to the village office, resulting in inefficiency. The aim of this research is to enhance the information service by developing a web-based information system utilizing AI through ChatGPT. The system development follows the prototype method with communication, planning, model design, prototype creation, and testing steps. The research results indicate that the developed system successfully meets user expectations. The system reflects high efficiency and effectiveness, with an average response time for short answers being approximately 1.99 seconds, while long answers require an average time of 12.04 seconds. Additionally, a questionnaire using the System Usability Scale (SUS) method involving 10 users obtained an average score of 87, indicating an "Excellent" level of satisfaction.